Measurement of Benzo [a]pyrene concentration in motor vehicle emissions using STM32F103-based TGS822 sensor - Hawa, Anjani Anil; Wardoyo, Arinto Yudi Ponco; Anggraeni, Dewi; A, Renetha Salma Myesha; Efendi, Yahya (Journal of Applied Science and Advanced Engineering, 2025)
Benzo[a]pyrene is one of the PAHs (Polycyclic Aromatic Hydrocarbons) pollutants originating from incomplete combustion or pyrolysis of organic materials. Benzo[a]pyrene is classified in GRUB 1 materials that have a carcinogenic impact on humans. Benzo [a]pyrene sources can be found in air, surface water, and soil. Benzo[a]pyrene can be sourced from motor vehicle emissions as a pollutant in the air. The incomplete combustion of fossil fuels used as motor vehicle fuel can be a source of Benzo[a]pyrene in the air. Therefore, research is needed to quantify the Benzo[a]pyrene concentration. This study aims to measure the concentration of Benzo[a]pyrene gas produced from motor vehicle emissions. The vehicle to be measured is two-wheeled vehicles with pertalite fuel. Vehicle smoke flows into the collection chamber through a hose with three different injection time durations. The measurement was conducted using a system based on the calibrated sensor of TG822. The average total concentration of B [a] P in the chamber depends on the injection time. The concentration is 63.572 ppb for 20s, 64.822 ppb for t40s, and 95.284 ppb for 60s.